2021
DOI: 10.1186/s12935-021-01777-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting androgen receptor signaling with MicroRNAs and Curcumin: a promising therapeutic approach for Prostate Cancer Prevention and intervention

Abstract: Prostate cancer (PC) is a multifactorial disease characterized by the abrogation of androgen receptor signaling. Advancement in microbiology techniques has highlighted the significant role of microRNAs (miRNAs) in the progression of PC cells from an androgen-dependent to an androgen-independent state. At that stage, prostate tumors also fail to respond to currently practiced hormone therapies. So, studies in recent decades are focused on investigating the anti-tumor effects of natural compounds in PC. Curcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Furthermore, it has also received attention from researchers due to its broad-spectrum antitumor activity. Some researchers have confirmed that it can prevent and treat prostate cancer by targeting the androgen receptor pathway (35). Both in vivo and vitro experiments have confirmed that it can improve the degree of genomic methylation in breast cancer cell lines (MDA-MB-231, MCF-7, T47D, etc.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has also received attention from researchers due to its broad-spectrum antitumor activity. Some researchers have confirmed that it can prevent and treat prostate cancer by targeting the androgen receptor pathway (35). Both in vivo and vitro experiments have confirmed that it can improve the degree of genomic methylation in breast cancer cell lines (MDA-MB-231, MCF-7, T47D, etc.…”
Section: Discussionmentioning
confidence: 96%
“…Since ancient times, the benefits of phytochemical curcumin have been applied in traditional medicine [47]. In recent years, several reviews highlighting various biological activities of curcumin have seen the light of day, indicating that curcumin is a green anticancer weapon [48][49][50][51][52][53][54]. The wide application of curcumin in cancer therapy has forced Kong et al [55] to ask whether "curcumin is the answer to future chemotherapy cocktail?".…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have validated some genes and related pathways contribute to PRAD, and some crucial genes may be potential biomarkers for diagnosis and treatment [8] , especially for non-coding RNAs (ncRNAs). As a class of potential important regulators, mainly including microRNA (miRNA), long-non-coding RNA (lncRNA) and circular RNAs (circRNA), has been widely concerned due to the key roles with mRNAs in ncRNA regulatory network.…”
Section: Introductionmentioning
confidence: 99%